2018
DOI: 10.1002/anie.201808229
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Reactivity of Stannane and Silane in the Trifluoromethylation of PdII: Cyclic Transition State versus Difluorocarbene Release

Abstract: The transmetalation is a key elementary step in cross-coupling reactions. Yet, the precise nature of its mechanism and transition state geometry are frequently elusive. This report discloses our study of the transmetalation of [Pd ]-F complexes with the silane- and stannane-based trifluoromethylation agents, R SiCF and R SnCF . A divergent reactivity was uncovered, with the stannane showing selective R-group transfer, and the silane selective CF -group transfer. Using a combined experimental and computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 76 publications
(29 reference statements)
0
23
0
Order By: Relevance
“…It is interesting here to compare the mechanism shown in Scheme 3 with the one obtained by Schoenebeck and coworkers for the transmetalation of [Pd II ]−F complexes with the Ruppert−Prakash reagent 8 to yield [Pd II ]−CF 3 intermediates. 19 In that case, the calculations showed that the reaction proceeds through a short-lived Pd-difluorocarbene intermediate.…”
Section: Resultsmentioning
confidence: 98%
“…It is interesting here to compare the mechanism shown in Scheme 3 with the one obtained by Schoenebeck and coworkers for the transmetalation of [Pd II ]−F complexes with the Ruppert−Prakash reagent 8 to yield [Pd II ]−CF 3 intermediates. 19 In that case, the calculations showed that the reaction proceeds through a short-lived Pd-difluorocarbene intermediate.…”
Section: Resultsmentioning
confidence: 98%
“…In 2018, Schoenebeck reported a decarbonylative trifluoromethylation of aroyl fluorides utilizing a Pd/Xantphos catalyst system and TESCF 3 as the trifluoromethyl source. 29 By computational methods, they proposed that the Pd(II) acyl complex (Xantphos)Pd(COPh)F is an intermediate efficiently undergoing transmetalation with TESCF 3 without external activation to form (Xantphos)Pd(COPh)CF 3 . Moreover, they found the activation energy for the reductive elimination step from this Pd(II)−CF 3 acyl complex to be lower than that for a decarbonylation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…19 F NMR (376 MHz, CD 2 Cl 2 ): δ (ppm) −17.0 (t, J = 13.6 Hz, 3F). 31 P and 19 F NMR spectra are consistent with literature data. , …”
Section: Methodsmentioning
confidence: 99%
“…[128][129][130][131] In such scenarios, Born-Oppenheimer molecular dynamics (BOMD) calculations on the QM-calculated PES can be used to generate a statistically representative number of trajectories from the transition states, as well as to monitor the dynamics of reactive events of relevant metal species. 132 In addition, quasi-classical molecular dynamics has been applied with great success in both organic reactions with bifurcation points and homogeneous transition metal catalysis. [133][134][135] For smaller systems, ab initio molecular dynamics (AIMD) can also be utilized.…”
Section: Study Of Ground-state and Excited-state Dynamical Behaviormentioning
confidence: 99%